Jejak Sukses Gerakan Kewirausahaan Sosial - Habsul Nurhadi (Majalah Ilmiah Bijak, 2019)
The social entrepreneurship movement in Indonesia, although generally equally aims to help improve the "comfort" of local life, but it turns out the form of activity is very diverse, depending on the availability of the superior carrying capacity that is in the local community. The social entrepreneurship movement in Indonesia is moving through the field of economic empowerment, through the field of family welfare, through the field of formal education of children, through the field of non-formal education, through the field of health, through the field of environmental sustainability, through the field of environmental hygiene / health; there are still many other fields of work.This study attempts to find information and analyze the typology-related mapping of the phenomenon of the social entrepreneurship movement that occurred in Indonesia. This study is still a preliminary study, as further studies are needed, such as to reveal what factors are driving the spirit of social entrepreneurship in society, what factors trigger unyielding spirit in solving the response community issues, and other useful and inspiring information.